A highly efficient Cu catalyst system for the radical reactions of α-bromocarbonyls. Issue 36 (21st April 2017) - Noda, Yushi; Nishikata, Takashi
Abstract : A Cu/TPMA and diisopropylamine system realized highly efficient atom-transfer radical reactions (substitution and cyclization). A maximum TON of up to 25 000 was achieved. Abstract : In this communication, we established highly efficient Cu-catalyzed ARGET-ATRS (atom-transfer radical substitution) of alpha-bromocarbonyls with styrenes to produce tert -alkylated styrenes. The maximum TON was up to 12 000. Hünig's base was very important to regenerate active Cu I . Moreover, a Cu-catalyzed C–C cleavage reaction via SH 2′ and intermolecular C–H cyclization of α-bromoimide was found.